PENDIDIKAN DAN PERTUMBUHAN EKONOMI ANTAR KABUPATEN DAN KOTA DI PROVINSI JAWA BARAT - Wardhana, Adhitya; Kharisma, Bayu; Ikhlasni, Zahra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.09.TAHUN 2020, 2020)
The education sector plays an important role for the development of a region. The measure of the success of improving the quality of human resources is by looking at the mean of year schooling. The increase in the mean of year schooling reflects the success of education policies in educating the public. This study analyzes the effect of mean of year schooling, life expectancy, government spending in the education and health sectors on economic growth in 26 districts / cities of West Java for the period 2012 - 2017. The method used is the Panel Data Regression Model. The results showed that all variables used in this study had a positive influence on economic growth in 26 districts / cities of West Java Province, where the mean of year schooling was the most statistically significant variable on economic growth in West Java Province.